Estudos taxonômicos e anatômicos em espécies de Passiflora L. (Passifloraceae s.l.) - Silva, Eduardo Oliveira (2020)
Passifloraceae Jussieu ex Kunth. has ca. 600 species distributed among 17 genera, of which Passiflora L. is the most species-rich. The family is distributed across tropical regions of the Americas, Africa and Asia. Brazil, one of its major centers of diversity, has approximately 150 species distributed among four genera: Ancistrothyrsus Harms, Dilkea Mast, Mitostemma Mast, and Passiflora. Passifloraceae species have high food, ornamental and medicinal potentials. However, taxonomic, anatomical and ecological studies on the group are scarce, especially regarding species distribution, foliar variability, and the nature and type of leaf secretory structures. Thus, in this study we approached taxonomic aspects of the group, which enabled us to report two new records of Passiflora to Brazil, namely P. auriculata Kunth to Tocantins state and P. cisnana Harms to Alagoas state. These two species are also reported herein as rediscovered to Maranhão state, as they have been recollected in the state territory several decades after the first documented records to the state. In addition, we performed an anatomical analysis on the foliar glands of three Passiflora species aiming to characterize gland morphology and anatomy; the analysis revealed important aspects of the ecological role these structures play in the relationships with the associated fauna, which allowed us to classify such structures as extrafloral nectaries.